1985
DOI: 10.1126/science.4001945
|View full text |Cite
|
Sign up to set email alerts
|

Defect in Vitamin B 12 Release from Lysosomes: Newly Described Inborn Error of Vitamin B 12 Metabolism

Abstract: Cultured diploid fibroblasts from a patient with a previously undescribed inborn error of cobalamin metabolism accumulate unmetabolized, nonprotein-bound vitamin B12 in lysosomes. These cells are able to endocytose the transcobalamin II-B12 complex and to release B12 from transcobalamin II. The freed vitamin B12 is not released from lysosomes into the cytoplasm of the cell. This suggests that there is a specific lysosomal transport mechanism for vitamin B12 in the human.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 12 publications
2
57
0
Order By: Relevance
“…This life-threatening condition is caused by defects in the LMBRD1 gene that encodes LMBD1 (Rutsch et al, 2009). The defect in lysosomal Cbl release was discovered 25 years ago, well before the likely transporter involved was characterised (Rosenblatt et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This life-threatening condition is caused by defects in the LMBRD1 gene that encodes LMBD1 (Rutsch et al, 2009). The defect in lysosomal Cbl release was discovered 25 years ago, well before the likely transporter involved was characterised (Rosenblatt et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…These pioneering studies also showed that chloroquine, a compound that increases lysosomal pH above its physiological level of ~ 4.5 thereby inhibiting lysosomal protease activity, prevents the release of Cbl from TCII and blocks the transport of lysosomal [ 57 Co]Cbl to both MS and MMCM (Rosenblatt et al, 1985). We have recently hypothesized that in addition to LMBRD1 mutations and drug-mediated alterations of lysosomal function that may trap Cbl in the lysosome, additional pathophysiological perturbations in lysosome function could also represent a "roadblock" for Cbl transit through the lysosomal compartment (Zhao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These include the cblA and cblB mutations, in which the synthesis of AdoCbl alone is impaired and patients present with cobalamin-responsive methylmalonic aciduria, and the cblC and cblD mutations, in which synthesis of both cobalamin coenzyme derivatives is impaired and patients present with combined methylmalonic aciduria and homocystinuria (3,4). Recently a patient has been described with a mutation, designated cblF, that affects translocation of free cobalamin from the lysosome to the cytoplasm (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…There is relatively little synthesis of AdoCbl or MeCbl and decreased function of both methylmalonyl-CoA mutase and methionine synthase. 8,9 CLINICAL REPORT The proband, the product of an unremarkable pregnancy, was a full-term female infant with a birth weight of 3175 g. There was no family history of metabolic disease or consanguinity. Her parents were of mixed white European descent, and she has a healthy older sister.…”
mentioning
confidence: 99%